The Influence of Work Environment, Motivation, and Discipline on Employee Performance at the Viqueque City Department, East Timor - Pinto, Olivio Pereira (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study explores the influence of work environment, motivation, and discipline on employee performance at the Viqueque City Department in East Timor. The research aims to identify how these factors contribute to the effectiveness and efficiency of employees in public service settings. By utilizing a quantitative approach, data was collected through surveys administered to 150 employees of the department, with a focus on their perceptions of the work environment, levels of motivation, and adherence to workplace discipline. The results indicate that both the work environment and motivation have a significant positive impact on employee performance, with motivation playing a key mediating role in enhancing the effects of the work environment. Additionally, discipline was found to be a strong determinant of consistent performance, particularly in terms of punctuality, task completion, and adherence to organizational protocols. The study also highlights the importance of creating a conducive work environment and fostering strong motivational strategies, alongside maintaining strict discipline, to improve employee productivity and performance in public sector institutions. This research contributes valuable insights for policymakers and management in designing effective strategies to optimize workforce performance at the Viqueque City Department and similar public institutions in East Timor.